2014
DOI: 10.2147/opth.s67984
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the relationship between corneal biomechanic and HbA1C levels in type 2 diabetes patients

Abstract: PurposeTo evaluate the corneal biomechanical properties due to the glycosylated hemoglobin (HbA1C) levels using the ocular response analyzer (ORA) in the patients with type 2 diabetes mellitus (DM).MethodsORA values were obtained from 156 eyes of subjects with type 2 DM and 74 eyes of healthy control subjects with similar age and sex. Subjects were divided into three groups: Group 1, healthy control subjects; Group 2, diabetes patients with HbA1C <7%; and Group 3, diabetes patients with HbA1C ≥7%. Corneal biom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
11
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 20 publications
(31 reference statements)
4
11
1
Order By: Relevance
“…Type 2 DM subjects also recorded significantly higher GAT measured-IOP, while ECDs were more significantly reduced than in healthy normal subjects ( Table 2 ). This finding is also consistent with previous reports on type 2 DM subjects [ 6 - 7 , 13 ] . Su et al [ 25 ] also observed that among Malays, those with diabetes and hyperglycemia showed significantly thicker central corneas, which were independent of age and IOP levels.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Type 2 DM subjects also recorded significantly higher GAT measured-IOP, while ECDs were more significantly reduced than in healthy normal subjects ( Table 2 ). This finding is also consistent with previous reports on type 2 DM subjects [ 6 - 7 , 13 ] . Su et al [ 25 ] also observed that among Malays, those with diabetes and hyperglycemia showed significantly thicker central corneas, which were independent of age and IOP levels.…”
Section: Discussionsupporting
confidence: 94%
“…Similar to previous reports [ 7 , 22 ] , the present study found that IOP was not correlated with CCT, ECD (after correcting for age) or with duration of DM that included all diabetic subjects. Measured CCT, ECD and IOP on the same subjects based on duration of diabetes are reported only in our study.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“… 9 , 12 , 18 A recent study comparing ORA data among 2 groups of diabetic patients (HbA1c <7%, HbA1c ≥7%) and healthy controls did demonstrate similar differential associations and found that IOPcc was not significantly different among the 3 groups, whereas IOPg was significantly higher in the diabetic patients than in the controls. 19 For smoking, findings have been variable, with some studies reporting no association 8 , 9 , 11 , 13 , 18 and other studies reporting higher IOP in smokers. 10 , 20 Among women, IOPg in this study was not significantly associated with smoking in univariable ( P = 0.004) or multiple regression ( P = 0.41, not shown in tables), a finding also seen in the Gutenberg Health Study using noncontact tonometry.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported thickening of central corneal thickness (CCT) in people with diabetes [ 5 , 6 , 7 , 8 ]. The basis for the association is unknown but one of the postulation is hyperglycaemia may cause corneal endothelial dysfunction with resultant stromal hydration and swelling of the cornea with some suggesting that this may be one of the earliest changes detectable in the diabetic eye [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%